The Influence of Compensation, Workload and Work Stress, on Employee Job Satisfaction, Case Study At PT Langganan Kita Bersama - Ester; Pujiarti (NIKAMABI: Jurnal Ekonomi dan Bisnis, 2023)
The purpose of this research is to determine the effect of compensation, workload and stress on employee job satisfaction, case study at PT Langgana Kita Bersama, both partially and simultaneously. This research is quantitative descriptive. The population of this research is employees of PT Langgana Kita Bersama. The sample for this research consisted of 31 respondents using interview data collection techniques. Data analysis methods include descriptive statistical analysis methods, validity and reliability tests, classical assumptions, statistical model tests, multiple linear regression analysis, T test, F test, coefficient of determination and slope in SPSS version 25. The research results show that the compensation variable has an effect on satisfaction employee work with a tcount score of 9.120 is greater than ttable 1.701, the workload variable has no effect on the job satisfaction of employees with a lower score. tcount value is -1.28 from ttable 1.701, the work stress variable has no effect on employee job satisfaction with a tcount value of 0.376 which is smaller than ttable 1.701, compensation, workload and work stress variables simultaneously influence employee job satisfaction with a fcount value of 30.394 , greater than ttable 2.96.